Regulation of lnc-TLCD2-1 on Radiation Sensitivity of Colorectal Cancer and Comprehensive Analysis of Its Mechanism - Yu, Qifeng; Zhang, Wei; Zhou, Xin; Shen, Wenqi; Xing, Chungen; Yang, Xiaodong (Frontiers in Oncology, 2021)
As is well known that colorectal cancer is the third most common cancer in the world, and radiation treatment plays a vital role in colorectal cancer therapy, but radiation resistance is a significant problem in the treatment of colorectal cancer. As an important member of the non-coding RNA family, long non-coding RNAs (lncRNAs) have been found that it plays a role in the occurrence and progression of colorectal cancer in recent years. However, little is known about the effect of lncRNA on colorectal cancer sensitivity to radiotherapy. We found that lnc-TLCD2-1 was significantly differentially expressed in radiation-tolerant CCL244 cell lines and radiation-sensitive HCT116 cell lines, suggesting that lnc-TLCD2-1 may regulate the radiosensitivity of colorectal cancer, and the relevant underlying mechanism was investigated. Cell clone formation assay, flow cytometry, and cell counting kit 8 (CCK8) were used to detect radiation sensitivity, apoptosis, and proliferation of colorectal cancer cells, respectively; Quantitative real-time PCR and western blot were used to detect the expression of genes; the direct interaction between lnc-TLCD2-1 and hsa-miR-193a-5p was verified by dual luciferase reporter assays; GEPIA, Starbase, TIMER and DAVID were used to complete expression of lnc-TLCD2-1, miR-193a-5p,YY1 and NF-кB-P65 in colorectal cancer, correlation, immune cell infiltration, GO and KEGG enrichment analysis. Clinical prognostic analysis data were obtained from GSE17536 dataset. After radiotherapy for HCT116, the expression of lnc-TLCD2-1 was increased, and the expression of hsa-miR-193a-5p was significantly decreased, while that of CCL244 was the opposite, and the change range of lnc-TLCD2-1 was relatively small. HCT116 with overexpression of lnc-TLCD2-1 after radiation treatment, the number of cell colonies significantly increased, and cell apoptosis decreased compared with the negative control group. The cell colonies and apoptosis of CCL244 with disturbed expression of lnc-TLCD2-1 were opposite to those of HCT116. Lnc-TLCD2-1 can regulate the expression of YY1/NF-кB-P65 by targeting miR-193a-5p. Lnc-TLCD2-1 can promote the proliferation of colorectal cancer. High expression of lnc-TLCD2-1 independently predicted a shorter survival. Lnc-TLCD2-1 is associated with radiation resistance and short survival in colorectal cancer patients. In addition, Lnc-TLCD2-1 can promote the proliferation of colorectal cancer. Our study provides a scientific basis for targeting lnc-TLCD2-1 in colorectal cancer radiation resistance interventions and selection of prognostic biomarker.